2015
DOI: 10.1039/c4tc02606c
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared photoluminescence of the univalent bismuth impurity center in leucite and pollucite crystal hosts

Abstract: aThe bismuth doped aluminosilicate phases leucite (KAlSi 2 O 6 ), gallium leucite (KGaSi 2 O 6 ) and pollucite (CsAlSi 2 O 6 ) display broadband NIR photoluminescence. The active center, responsible for this luminescence, is the Bi + monocation, which substitutes for the large alkali metal cations. The Al,Si-disorder in the aluminosilicate framework of studied crystal phases results in the heterogeneity of Bi + luminescent center population, which manifests itself in the characteristic dependency of the lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…We adopt here, that two bands in the visible range of the absorption spectrum and in the luminescence excitation spectrum of Bi + -doped ternary halides result from the excitation to the sublevels of crystal-field splitted 3 P 2 state, while the PL is the result of radiative transitions from the sublevels of the 3 P 1 state to the 3 P 0 ground state [9,11,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopt here, that two bands in the visible range of the absorption spectrum and in the luminescence excitation spectrum of Bi + -doped ternary halides result from the excitation to the sublevels of crystal-field splitted 3 P 2 state, while the PL is the result of radiative transitions from the sublevels of the 3 P 1 state to the 3 P 0 ground state [9,11,26].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that several of such subvalent bismuth forms (Bi + [4][5][6][7][8][9][10][11], Bi 5 3+ [12][13][14][15][16], Bi 2 8+ [16]) demonstrate the broadband NIR PL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed in both glass and glass-ceramics samples bismuth NIR emission centers can be stabilized. They show typical absorptions and extremely broad luminescence which spans from 1100 to 1600 nm [3][4][5][6][34][35][36] with full width at half maximum of~300 nm (see Figures 2 and 5). exhibit similar luminescence feature.…”
Section: Sr 2 Ybf 7 Nanocrystals Morphology and Bismuth Distributiomentioning
confidence: 99%
“…1 These materials have received extensive attention as a result of their peculiar characteristics including ultrabroad and long-lived photoluminescence (PL) covering the telecommunication and optimal biological optical windows, high emission quantum efficiency, and host-dependent spectral line shape. 1 Up to date, NIR PL has been observed in diverse classes of bismuth-activated materials such as glasses, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] conventional crystals, [16][17][18][19][20][21][22][23][24][25][26] molecular crystals, [27][28][29][30] ionic liquids, 31 and amorphous nanoparticles. 32 The use of these materials as optical gain media or biomarkers has been witnessed by functional demonstrations for optical fiber amplifiers, fiber lasers, and bioimaging.…”
Section: Introductionmentioning
confidence: 99%